"I Used to be Scared to Even Like Stand Beside Somebody Who Had It": HIV Risk Behaviours and Perceptions Among Indigenous People Who Use Drugs - Lavalley, Jennifer

(untitled) - Livingstone, Christopher; Steinhauer, Melissa; Goodman, Ashley; Kerr, Thomas (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
Objectives: In Canada, and elsewhere, Indigenous people who use illicit drugs and/or alcohol (WUID/A) experience a disproportionate burden of HIV-related harm. This study examined HIV risk perceptions and behaviours among Indigenous people WUID/A living in the Downtown Eastside (DTES) and the policies and practices that shape inequities and vulnerabilities for them in HIV testing and treatment. Further, we aimed to situate the vulnerabilities of Indigenous people WUID/A in HIV care within the context of wider structural inequality and generate recommendations for culturally relevant and safe HIV treatment options.Methods: This research employed an Indigenous-led community-based participatory approach using talking circles to explore experiences of Indigenous people living with HIV. Under the participatory research framework, community researchers led the study design, data collection, and analysis. Talking circles elicited participants’ experiences of HIV knowledge, testing, and treatment, and were audio-recorded and transcribed. Data were coded line-by-line and codes were organized into themes. Results: Five key themes were identified via the talking circles: evolving HIV risk perceptions (e.g., HIV knowledge and testing, and “intentional exposure”); research as an avenue for HIV testing; HIV treatment and discussions about grief and loss; HIV-related stigma and discrimination; and the importance of culturally-relevant and safe HIV treatment options for Indigenous people WUID/A.Discussion: Our work reveals that Indigenous people WUID/A do not have adequate access to HIV knowledge and education, often limiting their ability to access HIV testing and supports. Participant stories revealed both internalized and community stigma and discrimination, which at times compromised connection with participants' home communities. Further, our findings point to a failure in the public health system to deliver accessible HIV information to Indigenous Peoples, hence, many participants have solely relied on participation in community-based research studies in the Downtown Eastside (DTES) for HIV education and knowledge. There is an urgent need for accessible, culturally safe, and community-based education and treatment options for Indigenous people WUID/A within HIV care.